Trump’s mirror to Germany: A reflection on four years - Fröhlich, Stefan (2020)
In the run-up to the 2020 US presidential election, it is time to examine the impact of Trump’s presidency on various countries across the globe. How do different countries look back upon four years of President Trump? In this fifth episode of the Clingendael Spectator series “Four Years Trump: Taking Stock and Looking Forward”, Stefan Fröhlich states that German-American relations are at a low point, but that Trump has also held up a mirror to Germans that accurately reflects their vulnerabilities.<br